Aquaporins in platelet function. (3rd October 2021) - Agbani, Ejaife O.; Poole, Alastair W.
Abstract: Structurally, aquaporins (AQPs) are small channel proteins with monomers of ~ 30 kDa that are assembled as tetramers to form pores on cell membranes. Aquaporins mediate the conduction of water but at times also small solutes including glycerol across cell membranes and along osmotic gradients. Thirteen isoforms of AQPs have been reported in mammalian cells, and several of these are likely expressed in platelets. Osmotic swelling mediated by AQP1 sustains the calcium entry required for platelet phosphatidylserine exposure and microvesiculation, through calcium permeable stretch-activated or mechanosensitive cation channels. Notably, deletion of AQP1 diminishes platelet procoagulant membrane dynamics in vitro and arterial thrombosis in vivo, independent of platelet granule secretion and without affecting hemostasis. Water entry into platelets promotes procoagulant activity, and AQPs may also be critical for the initiation and progression of venous thrombosis. Platelet AQPs may therefore represent valuable targets for future development of a new class of antithrombotics, namely, anti-procoagulant antithrombotics, that are mechanistically distinct from current antithrombotics. However, the structure of AQPs does not make for easy targeting of these channels, hence they remain elusive drug targets. Nevertheless, thrombosis data in animal models provide compelling reasons to continue the pursuit of AQP-targeted antithrombotics. In this review, we discuss the role of aquaporins in platelet secretion, aggregation and procoagulation, the challenge of drugging AQPs, and the prospects of targeting AQPs for arterial and venous antithrombosis.